Effects of Polyphenols from Cocoa Powder on Diabetic Syndrome in Obese-Diabetic Rats - Mhd Jalil, Abbe Maleyki (2007)
This study was carried out to determine the effects of polyphenols from cocoa powder on diabetic syndrome of obese-diabetic (Ob-db) rats. The studied diabetic syndrome are fasting plasma glucose level, oral glucose tolerance test, insulin level and insulin sensitivity, lipid profiles (total cholesterol, triglycerides, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and free fatty acids), oxidative stress biomarker (8-isoprostane), and antioxidant enzymes (superoxide dismutase and catalase). Obese-diabetic (Ob-db) rats were developed using a high-fat diet (49% fat, 32% carbohydrate, and 19% protein from total energy, kcal) for 3 months, followed by a low dose (35 mg/kg body weight) streptozotocin (STZ) injection. Cocoa extract (600 mg/kg body weight) containing both polyphenols (2.17mg epicatechin, 1.52 mg catechin, 0.25 mg dimer and 0.13 mg trimer g/cocoa extract) and methylxanthines (3.55 mg caffeine and 2.22 mg theobromine g/cocoa extract) was given to the rats for 4 weeks. The results indicated that there were no significant differences in fasting plasma glucose, insulin level and insulin sensitivity after 4 weeks of cocoa extracts administration. Oral glucose tolerance test revealed that cocoa supplementation in Ob-db rats significantly (p < 0.05) reduced plasma glucose at 60 and 90 min compared to unsupplemented Ob-db rats. The supplementation significantly (p < 0.05) reduced the plasma total cholesterol, triglycerides and low-density lipoprotein cholesterol of obese-diabetic rats (Ob-db + cocoa) compared with non-supplemented animals (Ob-db). Plasma free fatty acid and oxidative stress biomarker (8-isoprostane) were significantly (p < 0.05) reduced after cocoa supplementation. Superoxide dismutase activity was enhanced in Ob-db compared to that in non-supplemented rats. However, no change was observed in catalase activity. Cocoa supplementation had an effect on postprandial glucose control but not for long-term glucose control (4 weeks). Four weeks of cocoa extract supplementation also possess hypocholesterolaemic properties. Moreover, cocoa supplementation could reduce circulating plasma free fatty acid and 8 isoprostane and may enhance the antioxidant defense system.